Algal polysaccharides: potential bioactive substances for cosmeceutical applications. (2nd January 2019) - Priyan Shanura Fernando, Ilekuttige; Kim, Kil-Nam; Kim, Daekyung; Jeon, You-Jin
Abstract: The cosmetics industry is one of the most profitable in the world today. This multi-billion-dollar industry has a profound sociological impact worldwide. Its influence is global, with most individuals being concerned with conserving their physical appearance, beauty, and youth. The consumers' desire for novel, better, and safer products has stimulated the utilization of natural-product-based cosmeceutical formulations over synthetic chemicals. With remarkable advancements in marine bioresource technology, algal polysaccharides have gained much attention as bioactive ingredients in cosmeceuticals. Algae biosynthesize a variety of polysaccharides including fucoidans, alginates, carrageenans, galactans, agar, porphyran, glucans, and ulvans, all of which exhibit distinctive structural and functional properties. Many of these materials have been proven to possess skin-protective effects, including anti-wrinkle, lightening, moisturizing, UV protective, antioxidative, and anti-inflammatory activity. Moreover, they have a wide spectrum of physicochemical properties, such as the ability to form hydrogels, which extend their utilization as emulsifiers, stabilizers, and viscosity controlling ingredients in cosmeceuticals. Accordingly, algal hydrocolloids and their synthetic derivatives can also be applied in tissue engineering and cosmetic surgery. The challenge is to increase awareness about these polysaccharides and consequently generate value-added products. This review discusses the beneficial biological and physicochemical properties of algal polysaccharides, highlighting their potential in cosmeceutical applications.